The Effect of Project-Based Learning on Pre-Service Chemistry Teachers’ Self-Efficacy and Critical Thinking Skills - Dwi Wahyudiati; Devi Qurniati (Postgraduate, University of Mataram, 2022)
The current research aims to: 1) determine the difference between self-efficacy (SE) and critical thinking skills (CTS) of pre-service chemistry teachers who were taught using the PjBL model; and 2) know how much the implementation of the PjBL model influences their self-efficacy (SE) and critical thinking skills (CTS). This experimental research was conducted through a quasi-experimental nonequivalent pretest-posttest control group design. The Cronbach's alpha coefficient value test for the validation of the instruments resulted in SE α = .86 and CTS α = .85. Manova test with a significance level of .05 was also performed to analyze the data. The results indicated: 1) there were significant differences in self-efficacy (SE) and critical thinking skills (CTS) before and after the implementation of the PjBL model, and 2) there was a significant effect of implementing the PjBL model on self-efficacy (SE) and critical thinking skills (CTS) with the contribution of the PjBL model of 35%. These results contribute to educational literature as an alternative solution for lecturers to apply the PjBL model in chemistry education learning in universities. Considering the characteristics of the learning material, students, and environmental conditions will maximize teamwork cooperation by using project-based activities to develop students' 21st-century skills.